Euskera, language of the Pyrenees: The case of Ansó (Aragon) and Roncal (Navarre) - Lopez-Mugartza Iriarte, Juan Karlos (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2008)
The valleys of Ansó and Roncal are located in a multilingual enclave in which, in addition to the presence of Aragonese and Euskera, Gascon is also much in evidence in its Béarnaise variety. The Ansó Valley joins the Roncal Valley at this point in the Pyrenees - the latter being the last Basque-speaking boundary of Basque-speaking Navarre. The outer borders of the Ansó Valley would appear to be dotted with lands that either know Euskera or have been considered part of Vasconia. We do not know what the Euskera spoken in Aragon was like, although it is also true to say that it would seem logical for there to have been some link with the nearest Basque dialects. There are no texts existing that could help us to understand what the Euskera from Aragon was like, but the presence of Euskera in Aragon is backed up mainly by toponymy. Indeed, toponymy is the only living linguistic witness that remains of Aragonese Euskera. The study of surnames from Ansó Valley and Roncal Valley is proof that the relationship between these two communities has been intense. So many centuries of close neighbourly relations with constant migratory movements in both directions, with marriages between people from both valleys, sharing common drover's road, was necessarily reflected in the languages of the place. In this article we study this common lexicon backed by toponymy and, also, the presence of Basque language in the Ansó's toponymy. We added the most important suffixes from the Euskera substratum in the toponymy of this area, and also, some Basque names used in composition and parasynthesis in the toponymy of Ansó (Aragon). We try to explain some phonetic matters of the Basque toponymy of Ansó through the toponymy of the Roncal Valley in Navarre, but the material available unables us to establish a direct relation between the toponymy of Roncal and Ansó, as the most characteristic Roncalese features have not been reflected in Ansó's toponymy. Nevertheless, it is undeniable that the place names of the two valleys have in common many phonetic and morphological features.